2013
DOI: 10.3899/jrheum.121390
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Causes of Death in an Unselected and Complete Cohort of Norwegian Patients with Systemic Sclerosis

Abstract: Compared to the Norwegian background population, our cohort of 312 unselected patients with SSc had decreased survival. The survival rates observed were, however, better than those previously reported from SSc referral centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
32
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 35 publications
8
32
2
Order By: Relevance
“…When we limited the definition of the inception cohort to those recruited within 1 year of disease onset, the SMRs were even higher, at 8.1 (95% CI 4.3–12.0) for the Australian cohort, 9.4 (95% CI 6.1–12.8) for the Canadian cohort, and 3.9 (95% CI 2.4–5.4) for the Spanish cohort. The values for Australian and Canadian 1‐year inception cohorts are much higher than those for the corresponding prevalent cohorts and higher than those reported from some previous studies , and they highlight the phenomenon of survivor bias, which leads to underestimation of the true burden of mortality in prevalent cohorts of subjects with SSc. This bias arises in large part because SSc has a substantial burden of early mortality with many deaths occurring within 5 years of disease onset, particularly in men and in the diffuse disease subtype.…”
Section: Discussioncontrasting
confidence: 62%
“…When we limited the definition of the inception cohort to those recruited within 1 year of disease onset, the SMRs were even higher, at 8.1 (95% CI 4.3–12.0) for the Australian cohort, 9.4 (95% CI 6.1–12.8) for the Canadian cohort, and 3.9 (95% CI 2.4–5.4) for the Spanish cohort. The values for Australian and Canadian 1‐year inception cohorts are much higher than those for the corresponding prevalent cohorts and higher than those reported from some previous studies , and they highlight the phenomenon of survivor bias, which leads to underestimation of the true burden of mortality in prevalent cohorts of subjects with SSc. This bias arises in large part because SSc has a substantial burden of early mortality with many deaths occurring within 5 years of disease onset, particularly in men and in the diffuse disease subtype.…”
Section: Discussioncontrasting
confidence: 62%
“…We found that age, being male and FVC were also independent predictors of mortality according to the multivariate analysis, and several previous studies have reported similar results . In one previous study, being male was associated with severe restrictive lung disease and baseline FVC was a predictor of fibrosis outcome .…”
Section: Discussionsupporting
confidence: 85%
“…We observed that high CCL21 levels were associated with reduced survival but appeared to have less influence on mortality compared with age at onset. This minor impact of CCL21 on mortality probably reflects that PAH, even though it is an important mortality risk factor, accounts for only 12% of all SSc deaths in Norway .…”
Section: Discussionmentioning
confidence: 99%